PERMIAN-TRIASSIC BOUNDARY INTERVAL AS A MODEL FOR FORCING MARINE ECOSYSTEM COLLAPSE BY LONG-TERM ATMOSPHERIC OXYGEN DROP - Weidlich O.; Kiessling W.; Flugel E. (My University, 2003)
Ecological traits of reefs across the Permian-Triassic boundary interval coincide with a modeled decline of atmospheric oxygen throughout the Permian Period. Selective extinction and recovery patterns within the reef system are observed both at the end of the middle Permian (end-Guadalupian) and at the Permian-Triassic boundary. The end-Guadalupian event selectively affected corals and broke down the cool-water carbonate factory. Sponges, however, were largely unaffected and bloomed in reefs toward the end of the Permian. The end-Permian total destruction of the metazoan reef system only left behind poorly diverse microbial communities. The temporal reef patterns are thus similar to spatial patterns of modern benthic communities approaching oxygen minimum zones. This observation suggests that a decline in oxygen concentrations was at least partly involved in the destruction of reefs, even where there is no direct evidence of oceanic anoxia.
Keywords: reefs; anoxia; mass extinction; recovery; Triassic; Permian; Guadalupian; Mesozoic::Triassic; Мезозой::Триасовая; Paleozoic::Permian::Guadalupian; Палеозой::Пермская::Гваделупский